PENGARUH PEMBELAJARAN TUTOR SEBAYA TERHADAP PRESTASI BELAJAR SISWA KELAS VII PADA POKOK BAHASAN SEGI EMPAT SEMESTER II SMPK IMMACULATA RUTENG TAHUN AJARAN 2018/2019” - Sebastianus Fedi; Maria Helena Ose Blikololong; Eufrasia Jeramat (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
This study aims to determine the effect of peer teaching model on the learning achievement of grade VII students, on the rectangular subject at SMPK Immaculata Ruteng, Flores, NTT. The research method was an experimental method, with post-test only control group design. Sampling of the experimental and control classes was carried out by a random class procedure, which preceded by an equivalence test through Anava. The research sample for the experimental class was 31 students, treated with peer tutoring learning models. And the research sample for the control class was 30 students, using conventional learning models. The instrument of this research was a test instrument in the form of description. The data analysis showed that the experimental group got an average value of 79,77 while the control group got an average value of 65,83. Calculation on data for the hypothesis test, we obtained = 4,1736 and = 1.6711. Because then is rejected and is accepted. In this case, = the average value of the learning achievement of the experimental class, while = the average value of the learning achievement of the control class. Means, student learning achievement taught by peer tutor learning models is higher than student learning achievement taught with conventional learning models. So, in an effort to build student mathematics learning achievement, peer tutoring learning models are more effective than conventional learning models. Keywords: Peer Teaching, Learning Achievement